Guests’ satisfaction with service quality provided by homestays in Selangor, Malaysia - Raju, Munieleswar (2015)
Homestay is a type of tourism program that permits the guests to rent a room from a local family so as to experience the lifestyle and culture of the locals. Thus, homestay tourism allows the general public or tenants of a village with available space or unoccupied rooms to rent out to tourists. Based on a report by MOTC, the number of homestays in Malaysia has increased since 2012. As at 2014, a total of 166 homestays have been established across all the states in Malaysia. Despite positive increase and economic contribution, the homestay program in Malaysia is faced with challenges stemming from many complaints and reports by both local and international guests about the low standard of accommodation facilities and services provided by homestay operators. Among the frequently reported complains are poor quality standards and sanitary systems, language barriers between the guests and host family which contributes to the low satisfaction level of guests. Also, homestay operators are reported to lack experience in providing good services and poor advancement in current technologies. Thus, this study was carried out with the main objective of investigating the satisfaction level of guests towards service quality of homestay. The specific objectives are 1) to identify the factors that influence guests to stay at homestay, 2) to determine the service quality of homestay using service quality (SERVQUAL) model, 3) to investigate the satisfaction level of the guests at homestay, and 4) to determine the effect of SERVQUAL dimensions and socio-demographic characteristics towards satisfaction level of guests at homestay. A total of 301 homestay quests (both locals and internationals) participated as respondents in this study. Responses were obtained by multi stage convenience sampling technique. All the homestays involved in the study were located in the state of Selangor and face-to-face interviews with the respondents were carried out using a structured questionnaire. The results revealed that the reason behind guests’ preference for homestay were the price, transportation, getting a new experience, good quality, convenient and food. The factors were measured based on a 7-points Likert scale. Based on factors analysis, five dimensions of service quality were revealed to influence the satisfaction level of guests at homestay namely assurance, responsiveness, reliability, empathy and tangible respectively. The total variance explained by these five dimensions is 78.39%. Furthermore, gap analysis was carried out to test the satisfaction level of guests towards service quality at homestay based on the five dimensions. These results implied that most guests were dissatisfied with the quality of services provided by the homestay operators. To further determine the effect of SERVQUAL dimensions and socio-demographic characteristics towards satisfaction level of the homestay guests, multiple linear regression analysis was conducted using 13 variables as independent variables against dissatisfaction level as a dependent variable. The dimensions of assurance, responsibility, reliability, empathy, tangible, age, income, level of education, and family size variables were observed to significantly influence guests satisfaction level. Based on the results, it showed that most of the guests were not satisfied with the services provided at the homestays in Selangor. Therefore, an improvement in government policy is urgently required to enforce better quality standards which would improve homestay quality and guests satisfaction level. The existing policy which is mainly focused on homestay operation in village should integrate quality assurance. Also, extension officers and relevant agencies should be proactive in carrying out knowledge transfer programs that emphasize guest’s expectation on homestay, current situation of tourism and importance of quality improvement in homestay to the operators of homestay. This is pertinent to the long term survival of the country’s tourism and homestay.